Assessing the South African National Health Insurance policy process from 2007 - 2019 - Mangwiro, Neville Taziva (My University, 2020)
Over a decade has gone by since the National Health Insurance (NHI) policy was put on the policy agenda when the African National Congress (ANC) passed a resolution to implement it. However, much of the discussion has focused on the design/content of the NHI and little attention has been put on the policy process and how it may have influenced the policy outcomes from 2007 to 2019. The purpose of this research is to assess the NHI policy process to examine the relationship between the nature of the process and the resulting policy outcomes. Elements of a systematic rapid review were adopted to conduct this study. The study took the form of a qualitative exploratory case study. Data collection involved document review using search words and various rapid review inclusion and exclusion methods to select documents. A Multiple Streams Framework (MSF) was adopted for the study. The study found that the elitist (topdown) approach taken by the government has been the main reason for the design/content of the NHI policy. Furthermore, the policy proposals themselves are very complex, which naturally slows completion of the process as the technical barriers to implementation become apparent. In large part these technical barriers are reflected through wide-ranging contestation from a significant spectrum of stakeholders. Also, the consultation process failed to meet its objectives, a feature that pervades the entire policy process to date. It was concluded that the NHI has a long way to go and that a more participative approach should be taken
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in the field of Public and Development Sector Monitoring and Evaluation to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2020
Keywords: National Health Insurance (NHI); South African National Health Insurance policy; Health Insurance; SDG-8: Decent work and economic growth